Diversity and species composition of fruit flies (Diptera: Tephritidae) in Lombok Island, Indonesia - syarron hudiwaku; Toto Himawan; Akhmad Rizali (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hudiwaku S, Himawan T, Rizali A. 2021. Diversity and species composition of fruit flies (Diptera: Tephritidae) in Lombok Island, Indonesia. Biodiversitas 22: 4608-4616. Fruit flies (Diptera: Tephritidae) are pests of several horticultural crops that can reduce the quality and quantity of fruit production. Information on fruit flies in Lombok Island, Indonesia, is still limited. However, it is predicted to have a high diversity of fruit flies because this island belongs to the Wallacea region. The aims of this research was to study the diversity and species composition of fruit flies in different habitat types in Lombok Island. The research was carried out on two habitat types, i.e., tropical rainforest and orchard with each habitat type consisted of three different sites that located spread across Lombok Island as replication. The research was carried out on two habitat types, i.e., tropical rainforest and orchard, with each habitat type consisted of three different sites spread across Lombok Island as replication. A sampling of fruit flies was conducted using parapheromone traps from March to June 2020. Twenty-two species and 210,267 individual fruit flies were collected from all locations during the study period. The most dominant species were Bactrocera carambolae, Bactrocera limbifera, Zeugodacus caudatus, and Bactrocera dorsalis. Based on the ANOVA, habitat types significantly affected the abundance but not the species richness of fruit flies. The visualization results obtained from the NMDS ordination indicated a difference in the species composition of fruit flies between the two habitats. In conclusion, habitat types are an essential factor in shaping the community of fruit flies in Lombok Island.